Kaizen and 5S Application from Lean Production Techniques Against Waste and Loss of Time in Production and Office Areas in a Food Business - ÇELEBİ, HASAN HÜSEYİN; YURT, UMUT CAN; Telli, Büşra (Springer Science and Business Media Deutschland GmbH, 2025)
The understanding of competition in businesses has become different as time passes. Lean philosophy is an inevitable approach to reduce cost, minimize downtime and shorten the process. In the most basic sense, lean philosophy is a culture that aims to improve issues such as order, order and speed in order to prevent waste, excessive workload, unbalanced workload, and loss of time. In this approach to improve processes, 5S is a frequently used technique. This technique has 5 steps. These steps are: sort, set in order, shine, standardize, and sustain. The biggest supporter of the application of this technique is the Kaizen method. Kaizen is a term that means change for the better. The factory we discussed in our study in Istanbul is a factory established to provide quality, healthy and affordable bread to the people of Istanbul. A lean philosophy is tried to be adopted in this factory, which continues to increase product quality by keeping costs low and keeping up with the developing technology and digitalizing world order. In our study, it is aimed to apply 5S and kaizen in order to reduce costs, alleviate the workload and save time in both production lines and offices in a food factory that produces bakery products within the borders of Istanbul. In our study, firstly, the places that were deemed inappropriate within the scope of 5S were identified and photographed together with Gemba walks and added to the Kaizen method file before and after. Then, by cooperating with the technical unit of the company and eliminating the nonconformities determined within the scope of 5S, it was determined how much profit these developments have achieved for the company.
International Symposium for Production Research, ISPR 2024
Keywords: 5S; Food; Kaizen; Lean philosophy; Production